B-learning: its influence in a communicative-approach EFL classroom, language department, University of Cuenca - Pacheco Salazar, Vicente Guillermo (2011)
This research has been done through an analytical and critical process, whose main objective is to determine the influence of B-learning, which stands for Blended Learning, in a Communicative-Approach English as a Foreign Language, EFL, classroom, Language Department, University of Cuenca, during the school trimester March - May. Constructivism was first in mind when creating virtual activities to teach English as a foreign language to fourth-level students at the University of Cuenca. Moodle was the main software used in order to teach the class with some other technological devices helping to create a virtual class, leading to B-learning. The virtual material created is there to promote motivation in the teaching faculty as well as in students, generating a multiplying effect.